FRI0354 Effects of Carbamylation and Citrullination of B and T Epitopes of Human Type II Collagen on Lymphocytes from Dr4+ Monozygotic Twins Discordant for Rheumatoid Arthritis. (10th June 2014) - De Santis, M.; Cavaciocchi, F.; Ceribelli, A.; Massarotti, M.S.; Meda, F.; Generali, E.; Selmi, C.F.
Abstract : Background: Rheumatoid arthritis (RA) susceptibility is linked to HLA DR4 and DR1. T cells in RA recognize the DR4/DR1-restricted epitope 261-273 of the human type II collagen, whereas B cells recognize the epitope 359-369. These epitopes can undergo post-translational modifications such as carbamylation and citrullination and both processes are involved in RA pathogenesis. Objectives: To investigate the role of B and T cell epitopes and their post-translational modifications on the adaptive immune response in the unique model of DR4 carrying monozygotic twins discordant for RA. Methods: PBMCs were obtained from a treatment-naïve HLA-DR4 positive woman with early RA (rheumatoid factor +, anti-CCP -, elevated CRP, bilateral wrist arthritis for 3 months) and from her healthy monozygotic twin sister (autoantibody-negative, normal CRP). Cells were cultured for 3 days with the native form of the collagen T epitope, its K264 carbamylated form (homocitT), the native form of the collagen B epitope, its R360 citrullinated form (citB) or a combination of the native and modified epitopes. After the stimulation, cells were analyzed by flow cytometry for activation, apoptosis, and cytokine polarization. Results: The activation of CD4 T cells was induced only with the modified B and T epitope stimulation in the RA twin (CD4+CD154+ in RA vs healthy; unstimulated: 1 vs 0.4%; T: 0.9 vs 1.6%; homocitT: 1.5 vs 0.7; B: 1 vs 0.6%; citB: 1.7 vs 0.1%, T + B: 0, 5 vs 0, 3%; homocitT + citB: 0, 9 vs 0, 4%). The antigen-activated CD4 T cells in the RA twin were significantly less apoptotic compared to unstimulated cells and the healthy twin (RA vs healthy; unstimulated: 37.5 vs 40%; T: 25 vs 24.1%; homocitT: 17 vs 50%; B: 30.8 vs 28%; citB: 13.9 vs 83.3%; T + B: 12.3 vs 63.6%; homocitT + citB: 19 vs 50%). Opposite from what observed in RA, the healthy twin manifested a higher increase in Th2 cells (CD4+CD154+IL4+ in RA vs healthy; unstimulated: 1.7 vs 2.1%; T: 2.9 vs 5.7%; homocitT: 3.6 vs 5.8%; T + B: 4 vs 4.9%; homocitT + citB: 3.9 vs 2.9%) compared to Th17 cells (CD4+CD154+IL17+ in RA vs healthy; unstimulated: 2.7 vs 1.7%; T: 4.1 vs 3.1%; homocitT: 4.5 vs 3.2%; T + B: 4.8 vs 3.5%; homocitT + citB: 5.5 vs 3%). In the healthy twin the Th2 increase was observed also in the antigen-activated CD8 T cells while B cell activation increased after different stimulations, but in all conditions activated B cells were apoptotic in 80% of the cases. Cytokine B cell production was not substantially altered with the epitope stimulations in the RA twin, while in the healthy twin there was a general increase in all cytokines. Conclusions: Our data obtained in the unique model of discordant monozygotic twins suggest that the exposure of collagen self-epitopes to lympocytes induces changes with pathogenic or protective effects that appear to be independent on DR4 and on post-translational antigen modifications. Further, this is associated with a greater Th17 shift in the antigen-activated CD4 T cells and with their enhanced resistance to spontaneous apoptosis in RA, while a greater Th2 shift is observed in the healthy twin. Carbamylation and citrullination of collagen epitopes may promote the activation of CD4 T cells. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4278